(untitled) (Raparin Journal of Humanities (RJH), 2026)
The research aims to: develop a scale to measure the problems and obstacles faced by football players from the audience’s perspective, and identify the obstacles and problems faced by football players from the audience’s perspective. The descriptive approach was chosen because it is appropriate for the nature of the research. The research community consists of fans who follow football matches in sports stadiums during the 2024-2025 season, numbering approximately 50,000 in Dohuk Province. The research sample was deliberately selected, numbering 508 individuals, representing 1.02% of the total population. A scale consisting of twenty-three items was created, and the discriminant validity and internal consistency of the scale were found, and the stability of the scale was determined. Statistical methods were used, including arithmetic mean, standard deviation, Pearson’s correlation coefficient, t-test for independent samples, and percentage to analyses the results and obtain the research objectives. After collecting the public’s opinions on the obstacles, the following results were obtained: A scale with high scientific validity (in terms of reliability, stability, and objectivity) was obtained, which can be used to identify obstacles and problems facing football from the audience’s point of view. The following obstacles were identified: 1- The following obstacles appeared repeatedly: a) Do injuries and suspensions affect the match and the players? b) Are the players affected?